The genus Cryptotendipes Beck et Beck in Florida, with the description of a new species (Diptera: Chironomidae: Chironominae) - Epler, J.h. (Zootaxa, 2018)
Species of the genus Cryptotendipes Beck et Beck in Florida are reviewed. Previous Florida records of C. casuarius (Townes) are shown to be misidentifications of C. emorsus (Townes). One species new for the state, C. pseudotener (Goetghebuer), is recorded and a new species, C. rutteri Epler, is described from pharate pupae and associated larval exuviae. Thus, a total of three species are known from the state. Keys are provided for adult males, pupae and larvae of these three species.